Irvine Luther Lenroot papers - Lenroot, Irvine Luther, 1869-1949.; Lenroot, Clara Clough, 1856-1942.
Correspondence, memoranda, speeches, reports, articles, political and subject files, legal records, biographical material, newspaper clippings, scrapbooks, printed matter, photographs, and other papers relating primarily to Lenroot's political campaigns and service as a Wisconsin state legislator and U.S. representative and senator; role in the Wisconsin Progressive movement; association with Robert M. La Follette; and relationship with national political leaders. Includes holograph notebooks concerning his congressional career and a typescript draft of his unpublished memoirs (1948). Papers of the Clough and Lenroot families include correspondence, genealogical material, and diaries and writings of Lenroot's wife, Clara Clough Lenroot. Correspondents include Calvin Coolidge, Charles Henry Crownhart, William H. Dougherty, Herman Lewis Ekern, Guy Despard Goff, John J. Hannan, William Hard, Warren G. Harding, Herbert Hoover, Walter Jodok Kohler, Robert M. La Follette, Henry Cabot Lodge, Gifford Pinchot, Alfred Thomas Rogers, and Mark Sullivan.
Jurist, lawyer, and U.S. representative and senator from Wisconsin.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Coolidge, Calvin, -- 1872-1933 -- Correspondence; Crownhart, Charles Henry, -- 1863-1930 -- Correspondence; Dougherty, William H. -- Correspondence; Ekern, Herman Lewis, -- 1872-1954 -- Correspondence; Goff, Guy Despard, -- 1867-1933 -- Correspondence; Hannan, John J., -- 1866-1946 -- Correspondence; Hard, William, -- 1878-1962 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Kohler, Walter Jodok, -- 1875-1940 -- Correspondence; La Follette, Robert M. -- 1855-1925.; La Follette, Robert M. -- 1855-1925 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Rogers, Alfred Thomas, -- 1873-1948 -- Correspondence; Sullivan, Mark, -- 1874-1952 -- Correspondence; Clough family; Lenroot family; United States. -- Congress; Wisconsin. -- Legislature; Political campaigns -- United States; Political campaigns -- Wisconsin; Political parties -- Wisconsin; Progressivism (United States politics); United States -- Politics and government -- 1901-1953.; Wisconsin -- Politics and government -- 1848-1950.; Jurists; Lawyers; Representatives, U.S. Congress -- Wisconsin; Senators, U.S. Congress -- Wisconsin